The patient competency rating scale as a measure of everyday functioning before and after traumatic brain injury : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Murphy, Latesha J (Massey University, 1996)
Impaired self awareness is a common outcome of traumatic brain injury (TBI) and is usually measured by comparing self and informant ratings of everyday functioning. The Patient Competency Rating Scale (PCRS; Prigatano et al. 1990), has often been used for this purpose. The present study compared the before and after PCRS ratings of 53 sets of TBI patients and their informants. These groups were also compared to 130 sets of self and informant ratings for a non-head injured control group. Comparison of self and informant ratings for before and after revealed that TBI subjects were very aware of their post injury difficulties. A comparison of the self ratings of TBI (before injury) and control subjects suggested that the TBI group performed better than the control group, which acknowledged some difficulty with controlling emotion. Informants generally rated TBI subjects (before injury) and control subjects as more competent than the subjects rated themselves. A comparison of informant and self ratings (after injury) demonstrated that subjects with severe head injuries underestimated their difficulties, whilst subjects in the mild and moderate groups tended to be aware of their difficulties or overestimated them. This finding suggests that degree of awareness is dependent on the severity of injury.
Keywords: Neuropsychological tests; Brain injury; Psychological testing; Personality disorders; Cognition disorders; Patient competency